2015
DOI: 10.1016/j.gore.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Endometrioid adenocarcinoma arising from deep infiltrating endometriosis involving the bladder: A case report and review of the literature

Abstract: HighlightsMalignant transformation of deep infiltrating endometriosis involving the bladder is quite rare.We review eight relevant cases which have been reported.This is the second case fulfilling Sampson and Scott criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…[6] Patients with endometriosis at the urinary bladder frequently present with urinary frequency and if longstanding may present with hematuria due to the deep endometriotic infiltration. [78] This is in keeping with our patient whose initial hematuria was overlooked. This case highlights the benefits of 18F-FDG PET/CT in our management planning, by excluding distant metastasis to the liver and identifying the nature of the soft tissue mass at the right posterolateral wall of the urinary bladder.…”
supporting
confidence: 85%
“…[6] Patients with endometriosis at the urinary bladder frequently present with urinary frequency and if longstanding may present with hematuria due to the deep endometriotic infiltration. [78] This is in keeping with our patient whose initial hematuria was overlooked. This case highlights the benefits of 18F-FDG PET/CT in our management planning, by excluding distant metastasis to the liver and identifying the nature of the soft tissue mass at the right posterolateral wall of the urinary bladder.…”
supporting
confidence: 85%
“…Recently, Yang et al reported and reviewed the 10 cases of malignant tumors located in the rectovaginal septum related to endometriosis [ 13 ]. Although even more rare, Tarumi et al reported and reviewed 9 cases of malignant transformation arising from DIE in the bladder [ 14 ]. The histological type of the malignancy that occurred was endometrioid and clear cell adenocarcinoma in both the rectovaginal septum and the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Although even more rare, Tarumi et al reported and reviewed 9 cases of malignant transformation arising from DIE in the bladder [14]. The histological type of the malignancy that occurred was endometrioid and clear cell adenocarcinoma in both the rectovaginal septum and the bladder.…”
Section: Discussionmentioning
confidence: 99%